Investigating the connectivity of Geshere and Rishiwa younger granite using aero-radiometric data - YUSUF BELLO; Kola Muideen Lawal; S. S. Magaji; J. Raimi; T. O. Amuda; D. Daramola; M. B. Yakubu; HA Lawal (Proceedings of the Nigerian Society of Physical Sciences)
Geshere and Rishiwa Younger Granites (YGs) are physically two separate bodies and are believed to be either from the same source or one is an extension of the other. Previous work suggests they could be connected at the subsurface, but the use of radiometric data can provide clarity as it reflects rocks' geochemical formation. This work focused on identifying possible connection between the two YGs based on the variation of the radioelements in the study area. The result shows the values of potassium, thorium, and uranium range from 0.1 to 4.9 %, 11.9 to 61.2 ppm, and 1.4 to 10.3 ppm respectively, which are lower to the range of the radioelements (that of potassium is comparatively close) reported in part of Egypt. The average potassium concentration around Geshere and Rishiwa is high (4.5 and 4.1 % respectively), thorium is low (13.1 and 14.9 ppm respectively), and uranium is low around Geshere and south of Rishiwa YGs, but high at north of Rishiwa YG. The composite maps of the three radioelements and the potassium reveal the extent of the YGs. The Th/K map indicates the two YGs are connected. Moreover, the composite maps of thorium, and uranium suggested the south of Rishiwa and Geshere share similar geochemistry. Geochemical analysis is recommended on rock samples of a region west of the Gehere YG which is a Pan-Africa Basement Complex but shows anomalies similar to the YGs.